Relationship between High School National Exam Scores and College Admission Test Scores in Indonesia - Herlina Karjo, Clara; Andreani, Wiwik (International Journal of Psychosocial Rehabilitation, 2020)
The focus of English instruction given in high schools and universities in Indonesia differs; thus, the exams given are not parallel either. English in high school basically focuses on reading comprehension, while in most universities students are prepared to take standardized tests such as TOEFL or IELTS. This paper aims to investigate if there is a correlation between the high school national exam scores and college admission test scores for the English subject of first-year university students in Jakarta and to find out the differences between both tests. The participants were 200 first-year university students from two private universities in Jakarta. The data were two kinds of English test scores from the High School National Exam (HSNE) and the College Admission Test (CAT), which was given in the form of a TOEFL-like test. To calculate the data, two sets of statistical analysis were performed, i.e., correlation and regression analysis. Besides the quantitative analysis, a qualitative study was also conducted regarding the English skills being tested in both tests. The results show HSNE scores significantly higher than CAT scores, denoting that the HSNE test was easier than the CAT test. Moreover, HSNE scores only gave a low contribution to the attainment of CAT scores, indicating that high school students were not properly prepared for college education, especially in English. This study implied that English subjects given in high school should prepare students for studying in university.